American Indian literature and the Southwest : contexts and dispositions - Anderson, Eric Gary, 1960- (University of Texas Press, 1999)
Explores a range of conceptions of the Southwest as reflected in American Indian literature and its interactions with, and interpretations by, Anglo literature.